2017
DOI: 10.1371/journal.pone.0187765
|View full text |Cite
|
Sign up to set email alerts
|

MRI-defined paraspinal muscle morphology in Japanese population: The Wakayama Spine Study

Abstract: ObjectiveThis study aimed to establish sex- and age-dependent distributions of the cross sectional area and fatty infiltration ratio of paraspinal muscles, and to examine the correlation between paraspinal muscle degeneration and low back pain in the Japanese population.MethodsIn this cross-sectional study, data from 796 participants (241 men, 555 women; mean age, 63.5 years) were analyzed. The measurement of the cross sectional area and fatty infiltration ratio of the erector spinae and multifidus from the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 43 publications
8
67
0
1
Order By: Relevance
“…While it is well established that muscle morphology is influenced by anthropometric factors, such as age, sex, physical activity levels, and body composition, [12][13][14][15] body mass index (BMI) remains the most frequently used variable to adjust for inter-subject variability in both anthropometric and body composition differences. BMI is, however, a poor indicator of body composition, especially in athletic populations, due to its inability to differentiate between lean and fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…While it is well established that muscle morphology is influenced by anthropometric factors, such as age, sex, physical activity levels, and body composition, [12][13][14][15] body mass index (BMI) remains the most frequently used variable to adjust for inter-subject variability in both anthropometric and body composition differences. BMI is, however, a poor indicator of body composition, especially in athletic populations, due to its inability to differentiate between lean and fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is well recognized that LBP leads to motor-control impairments and altered body kinematics, which can present as a wide array of dysfunctions, including hypomobility or hypermobility of the involved lumbar segments, changes in paraspinal muscle recruitment and coordination, and movement fear or avoidance. 5 Paraspinal muscle morphologic changes (eg, atrophy, [6][7][8] asymmetry, 6,9 fatty infiltration), 10,11 especially of the lumbar multifidus (LM) muscle, and functional deficits 12 (eg, altered muscle activity) have also been reported in patients with LBP. The LM muscle plays a critical role in providing spinal stability during trunk movement and spine proprioception, 2 which likely become impaired when atrophy, fatty infiltration, or both are present.…”
mentioning
confidence: 99%
“…Morphological measurements can be taken in the longitudinal axis or the transversal axis. In the transversal axis, observational studies [ 26 , 27 ] and a systematic review [ 28 ] have shown that MR has a high correlation between morphological changes and pathology or pain. However, to the best of our knowledge, there are no studies of longitudinal axis evaluation using MRI.…”
Section: Discussionmentioning
confidence: 99%